Wymiary transfikcjonalności - Maj, Krzysztof M. (Przestrzenie Teorii, 2019)
The article Facets of Transfictionality delivers a concise analysis of the newly-introduced narratological concept of “transfictionality” (put forward by Richard Saint-Gelais in the early 2000s). The author discusses the phenomenon as emerging on the border between the text-centred poetics of classical narratology and the world-centred poetics of postclassical narratology by use of Jan-Noël Thon’s and Marie-Laure Ryan’s project of “media-conscious narratology”. Defined as such, transfictionality allows the contemporary phenomena of retelling or cross-over to be described without the necessity of reproducing fan-made concepts and terms of such ilk, and instead rooting them in established theoretical constructs, such as narrative metalepsis. Consequently, the article illustrates the postclassical theory of narrative and the theory of literature with examples more common to media studies, with the aim being to emphasise Ryan’s thesis that transmediality is only a specific case of transfictionality, and that the latter is a far older and better acknowledged concept what is generally understood as the theory of fiction. Moreover, the text follows up on Saint-Gelais’ inspirations derived from Umberto Eco’s cultural semiotics and proposes to introduce an Eco-inspired concept of “xeno-encyclopaedic competence” in order to determine a specific recipient’s competence that allows them to move across not only media or texts but also imaginary worlds, which consequently become their fictional habitats.